1995
DOI: 10.1097/00003446-199510000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Listening, Event-Related Potentials, and Interhemispheric Transfer in the Elderly

Abstract: Objective: To determine the basis for the large, age-related asymmetries in dichotic listening performance scores reported by Jerger et al. (1994).Design: Behavioral and electrophysiologic responses to dichotic listening tasks in both verbal and nonverbal paradigms were obtained in four groups of subjects: young adults with normal hearing, elderly persons with presbyacusis, elderly persons with presbyacusis and marked dichotic deficits, and patients with lesions of the corpus callosum.Results: In comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 14 publications
9
41
0
7
Order By: Relevance
“…This reduced left hemisphere input could be associated with the maturation of myelin in the corpus callosum and in related pathways. A lack of callosal input to the left hemisphere has been shown in secondary topographic mapping to possibly be the result of degeneration (demyelination) of the corpus callosum in relation to aging (37). In addition, one of the training procedures employed in this study was dichotic interaural intensity difference training.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced left hemisphere input could be associated with the maturation of myelin in the corpus callosum and in related pathways. A lack of callosal input to the left hemisphere has been shown in secondary topographic mapping to possibly be the result of degeneration (demyelination) of the corpus callosum in relation to aging (37). In addition, one of the training procedures employed in this study was dichotic interaural intensity difference training.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Several studies also found an age-related decrease of LE performance (Alden et al, 1997;Bellis & Wilber, 2001;Bouma & Van der Endt, 1993;Hallgren et al, 2001;Jerger et al, 1994Jerger et al, , 1995Strouse et al, 2000aStrouse et al, , 2000b.…”
Section: Increased Asymmetry In Recall Performance In Elderlymentioning
confidence: 94%
“…Indeed, research has demonstrated that the DLT performance of elderly is decreased compared to younger participants (Alden, Harrison, Snyder, & Everhart, 1997;Bouma & Van der Endt, 1993;Gelfand, Hoffman, Waltzman, & Piper, 1980;Hallgren, Larsby, Lyxell, & Arlinger, 2001;Martin & Cranford, 1991;Strouse, Wilson, & Brush, 2000a). Also, an age-related increase of ear asymmetry has been reported: performance of the LE has been found to decrease stronger than performance of the RE (Jerger, Alford, Lew, Rivera, & Chmiel, 1995;Jerger, Chmiel, Allen, & Wilson, 1994;Strouse et al, 2000a;Strouse, Wilson, & Brush, 2000b). However, this finding is still controversial since some aging studies have failed to find such an effect (Gelfand et al, 1980;Martini et al, 1988) or found that age effects could only be perceived in focussed attention conditions, in particular when attention had to be focussed at the LE (Alden et al, 1997;Bouma & Van der Endt, 1993;Hallgren et al, 2001).…”
mentioning
confidence: 99%
“…The elderly have a worse performance in low redundancy hearing tasks, in dichotic hearing tasks and in temporal pattern tasks when compared to adult individuals and such findings could indicate impairment in central auditory pathways 1,[5][6][7][8][9][10][11] . Right ear advantage (REA) seen in dichotic listening tests, was considered as stemming from an impairment of the inter-hemispheric auditory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Right ear advantage (REA) seen in dichotic listening tests, was considered as stemming from an impairment of the inter-hemispheric auditory pathways. [8][9][10][11] Auditory processing assessment information is important to identify functional deficits that could be associated to difficulties in speech understanding 12 , in audiologic rehabilitation/training 13 and to check the results of treatment interventions 14 . Ipsilateral synthetic phrases identification test with competitive message (SSI/MCI), frequency patterns test (PPS) and the alternate dissyllable by dichotic task test (SSW) are behavioral sensitive tests, with specificity, reliability and facility to use in certain lesions or dysfunctions of the different areas of the auditory central nervous system (ACNS).…”
Section: Introductionmentioning
confidence: 99%